1971
DOI: 10.1017/s004317450004889x
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine-Soil Organic Matter Interactions

Abstract: Adsorption capacities of Walla Walla silt loam soil for 2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine (atrazine) were determined after each extraction with ethyl ether, ethyl alcohol, and hot water. The results suggested that the ether and alcohol-extractable components of the soil organic matter, i.e. fats, oils, waxes, and resins, had a negligible capacity to adsorb atrazine but that hot-water-extractable materials, i.e. polysaccharides, had a small adsorptive capacity. of the compounds chosen to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…The present results are at odds with previous findings which suggested that the incorporation of organic amendments in soil increased TA persistence by increasing adsorption 27, 33. However, the nature of the organic amendment has a crucial effect on pesticide adsorption and persistence 34…”
Section: Resultscontrasting
confidence: 99%
“…The present results are at odds with previous findings which suggested that the incorporation of organic amendments in soil increased TA persistence by increasing adsorption 27, 33. However, the nature of the organic amendment has a crucial effect on pesticide adsorption and persistence 34…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies showed that properties of organic amendments are an important factor in affecting pesticide sorption in amended soils (Dunigan and MacIntosh 1971;Dolaptsoglou et al 2007;Luo et al 2009). Biochar is also known as black carbon that is derived from biomass.…”
Section: Treatmentmentioning
confidence: 99%
“…The adsorption of atrazine and alachlor on both organic and inorganic soil constituents has been widely studied [7,8] and is well correlated with organic matter and clay content. Soil pH, temperature, moisture content, exchangeable cations, and electrolyte concentration also affect the adsorption and deg-* To whom correspondence may be addressed (jstucki@uiuc.edu).…”
Section: Introductionmentioning
confidence: 99%